(untitled) (Comprehensive Journal of Science, 2025)
This study focuses on the design and implementation of a 5G Radio Access Network (5G RAN) using open-source platforms, specifically srsRAN in combination with SDR devices, within a Standalone (SA) architecture. The functional split of the radio node was applied into CU/DU/RU units, which were physically integrated with the core network through standard interfaces (NG, F1). The experimental scenario involved connecting a virtual phone using SDR to the radio network, thereby enabling the emulation of an end-user connection. The results demonstrated successful registration and establishment of a PDU Session between the user and the network, with stable performance observed in the downlink (DL), where appropriate CQI values were achieved alongside suitable data rates and nearly negligible error rates. In contrast, the uplink (UL) showed less stability due to the limited transmission power of the user equipment, as reflected in fluctuating signal levels and higher error rates in certain cases. These findings confirm the feasibility of deploying 5G RAN networks using open-source tools, offering a practical and flexible testbed that not only supports academic research but also paves the way for future innovations in next-generation mobile networks.